PENGEMBANGAN MULTIMEDIA PEMBELAJARAN TEMATIK SEKOLAH DASAR BERBASIS BUDAYA LOKAL MASYARAKAT FLORES - Laksana, Dek Ngurah Laba (Universitas Nusantara PGRI Kediri, 2017)
Abstract: The aimed of this study was to development a multimedia learning with content and context based on local culture of Ngada Flores that can be used in teaching in elementary schools. Multimedia learning is developed with the ADDIE model (analyze, design, development, implementation, and evaluation). This research was conducted in Ngada East Nusa Tenggara province. Subjects in this study is the Curriculum 2013 as well as teachers and students of grade fourth in District Bajawa Ngada, East Nusa Tenggara. The data collected in this study were analyzed by descriptive qualitative to describe the effectiveness of multimedia to be developed. The results showed that (1) multimedia that is developed is a multimedia thematic, namely Themes Cultural Diversity Nation, (2) there are some cultural content areas integrated into multimedia, among other local dance and folk songs, and (3) developed thematic multimedia integrated local culture of Ngada is in the excellent category is based on an expert assessment and testing to elementary students. Key words: multimedia learning content and context of culture, Ngada Abstrak: Tujuan dari penelitian ini adalah untuk menghasilkan multimedia pembelajaran berbasis konten dan konteks budaya lokal masyarakat Ngada Flores yang dapat digunakan dalam pembelajaran di sekolah dasar. Multimedia pembelajaran ini dikembangkan dengan model ADDIE (analyze, design, development, implementation, dan evaluation). Penelitian ini dilakukan di Kabupaten Ngada Provinsi Nusa Tenggara Timur. Subjek dalam penelitian ini adalah kurikulum 2013 kelas IV serta guru dan siswa SD kelas IV di Kecamatan Bajawa Kabupaten Ngada, Nusa Tenggara Timur. Data yang telah dikumpulkan dalam penelitian ini dianalisis secara deskriptif kualitatif untuk menjelaskan efektivitas multimedia yang akan dikembangkan. Hasil penelitian menunjukkan bahwa (1) multimedia yang dikembangkan adalah multimedia tematik, yaitu Tema Keragaman Budaya Bangsaku, (2) terdapat beberapa konten budaya daerah yang diintegrasikan ke dalam multimedia, antara lain tari daerah dan lagu daerah, dan (3) multimedia tematik yang dikembangkan terintegrasi budaya lokal Masyarakat Ngada ada dalam kategori sangat baik berdasarkan penilaian ahli dan uji coba kepada siswa SD. Kata kunci: multimedia pembelajaran, konten dan konteks budaya, Ngada